2011
DOI: 10.1007/s10557-010-6278-0
|View full text |Cite
|
Sign up to set email alerts
|

Rationale for Combining a Direct Renin Inhibitor with other Renin- Angiotensin System Blockers. Focus on Aliskiren and Combinations

Abstract: Inhibition of the renin-angiotensin system has been a highly successful therapeutic approach for the prevention of hypertension-related end organ damage. Angiotensin converting enzyme inhibitors and angiotensin II receptor blockers lower blood pressure and reduce morbidity and mortality in patients with cardiovascular and kidney disease. However, progression to end-stage disease remains common in these patient populations. A compensatory increase in plasma renin activity occurs with the use of either angiotens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 98 publications
(119 reference statements)
1
4
0
Order By: Relevance
“…Nevertheless, aliskiren does increase renin levels (Feldman, et al, 2008), suggesting activation of a feedback network to the RAS. Consistent with these findings, clinical data show that aliskiren works better when combined with other antihypertensive drugs (Azizi, et al, 2004; O’Brien, et al, 2007; Siragy, 2011). Evidence that the PRR—the newly discovered RAS component that mediates both Ang II formation and Ang II-independent intracellular signaling—plays a significant role in the development of hypertension and cardiovascular end-organ damage through prorenin (Ichihara, Itoh, & Inagami, 2008) suggests that the PRR might be a promising new target for the treatment of hypertension.…”
Section: The Development Of Prr Antagonistssupporting
confidence: 68%
“…Nevertheless, aliskiren does increase renin levels (Feldman, et al, 2008), suggesting activation of a feedback network to the RAS. Consistent with these findings, clinical data show that aliskiren works better when combined with other antihypertensive drugs (Azizi, et al, 2004; O’Brien, et al, 2007; Siragy, 2011). Evidence that the PRR—the newly discovered RAS component that mediates both Ang II formation and Ang II-independent intracellular signaling—plays a significant role in the development of hypertension and cardiovascular end-organ damage through prorenin (Ichihara, Itoh, & Inagami, 2008) suggests that the PRR might be a promising new target for the treatment of hypertension.…”
Section: The Development Of Prr Antagonistssupporting
confidence: 68%
“…However, it is unclear whether ALK may effectively induce regression of cardiac hypertrophy. Although the combination of ALK with an ACEI or an ARB can synergistically attenuate both 1006 www.nature.com/aps Weng LQ et al Acta Pharmacologica Sinica npg hypertrophy and dysfunction in hypertensive patients [8,9] , a systematic review of randomized, controlled clinical trials has shown that combined therapy is associated with a higher risk of hyperkalemia than monotherapy with an ACEI, an ARB or ALK [10] . In addition, some patients are intolerant of ACEI or ARB, whereas ALK is well tolerated [11] .…”
Section: Introductionmentioning
confidence: 99%
“…Angiotensinogen is the only known substrate for renin;2, 5 this renders renin of extreme importance regarding selectivity and enzyme specificity. Mature renin is a 340‐amino acid, pepsin‐like enzyme.…”
Section: Introductionmentioning
confidence: 99%